On the M‐essential spectra of two‐group transport equations. (12th September 2013) - Walha, Ines
Abstract In this paper, we deal with the M‐essential spectra of unbounded linear operators in Banach spaces where some generalizations of earlier work are given. Furthermore, we give an application from transport theory. Copyright © 2013 John Wiley & Sons, Ltd.